The cost of alternative urban water supply and efficiency options in California. (28th May 2019) - Cooley, Heather; Phurisamban, Rapichan; Gleick, Peter
Abstract: Urban communities, farms, businesses, and natural ecosystems depend upon adequate, reliable, and affordable supplies of clean water. As populations and economies grow and as climatic changes alter both water supply and demand, traditional options for meeting freshwater needs are becoming less available, reliable, and effective. As we approach peak water constraints on traditional water supplies, more efforts needed to reduce water demands through a wide range of conservation and efficiency technologies and policies, and to develop alternative, non-traditional water sources. A key factor in the adoption of these strategies is their economic feasibility; yet, only limited and often confusing data are available on their relative costs. To fill this gap, this analysis evaluates the costs of four groups of alternatives for urban supply and demand based on data and analysis in the California context: stormwater capture; water recycling and reuse; brackish and seawater desalination; and a range of water conservation and efficiency measures. We also describe some important co-benefits or avoided costs, such as reducing water withdrawals from surface water bodies or polluted runoff in coastal waterways. While difficult to quantify, such benefits are economically relevant, and we highlight areas where further research and analysis are needed to improve estimates presented here. All of the water-use efficiency options are far less costly than traditional or alternative supply systems with the exception of some of the most expensive landscape water reduction options. The water treatment and reuse systems and the urban stormwater capture projects are more costly per unit of water produced but still less expensive than seawater desalination—the most expensive option evaluated.